Definitive salvage radiation therapy and chemoradiation therapy for lymph node oligo-recurrence of esophageal cancer: a Japanese multi-institutional study of 237 patients. Issue 1 (December 2017) - Yamashita, Hideomi; Jingu, Keiichi; Niibe, Yuzuru; Katsui, Kuniaki; Matsumoto, Toshihiko; Nishina, Tomohiro; Terahara, Atsuro
Abstract Background This study evaluated the treatment results of lymph node (LN) oligo-recurrence in esophageal cancer patients treated with salvage radiotherapy (RT) in a multi-institutional retrospective study. Methods Eligibility criteria for this retrospective analysis were: the primary lesion of esophageal cancer was controlled; from one to five LN recurrences; total RT dose ≥45 Gy to exclude palliative RT; without recurrence other than LN; and salvage RT for LN recurrence was given between January 2000 and April 2015. The median follow-up time for the 93 living patients was 29.6 months. Results Two hundred thirty-seven patients were matched in five hospitals. The 3-year overall survival (OS) was 37%, local control was 45%, progression-free survival was 24%, and esophageal cancer-specific survival was 42%. On univariate analysis for OS, combined chemotherapy (p = 0.000055), disease-free interval (DFI) ≥12 months (p = 0.0013), LN max diameter ≤22 mm (p = 0.0052), and Karnofsky performance status ≥80% (p = 0.030) were associated with a significantly better prognosis. On multivariate analysis, significant differences were seen for combined chemotherapy (p = 0.000018), DFI (p = 0.0027), and LN max diameter (p = 0.018). Conclusions LN oligo-recurrence following treatment for esophageal cancer was not a terminal-stage event. Moreover, cure may be possible by chemoradiation therapy with a long DFI (≥12 months) and small size (≤22 mm).